PENGARUH VARIASI JUMLAH BLADE TERHADAP AERODINAMIK PERFORMAN PADA RANCANGAN KINCIR ANGIN 300 Watt - I Made Adi Sayoga; I Kade Wiratama; Made Mara; Agus Dwi Catur (Dinamika Teknik Mesin, 2014)
In some areas in Indonesia, such as: the southern part of Sumatra until Nusa Tenggara, wind velocity is large enough to be used as a wind power plant with a range of 5-15 knots of wind speed equivalent 2.5-7.5 m / s. However, wind energy has not yet been developed, there are only a wind power plant with a total capacity of 1.4 GW in Indonesia.  Mostly, instruments wind power is basically intended for European plains wind speed range of 10-30 knots. So that the necessary adjustments for the Indonesian state that smaller wind speed in order to optimize the system work.The purpose of this study was to determine the influence of the number of blades and wind speed on electric power generated by a horizontal axis wind turbine. The type of blade used is arched plate and fitted with a pitch angle of 30o. Key issues to be examined in this study is how the influence of the number of blades (3, 4, and 5 blade) and wind speed (3m / s, 4m / s and 5 m / s) to the performance of horizontal axis wind turbines.These results indicate that the number of blade 5 gives rpm, torque, power and highest Cp compared to the number of blade 3 and 4. Similarly, the wind speed of 5m / s provide better performance on any number of blade. The highest power obtained on the number of blades 5 and wind speed of 5 m / s with an average of 23.775 Watt. The highest Cp values obtained on the number of blades 5 and wind speed of 5 m / s which is an average of 0.4.